Molecular docking studies of synthesized benzimidazole derivatives as Hepatitis C virus NS5B inhibitors : - Huỳnh, Duy Thiện (Trường Đại học Cần Thơ, 2019)
In the field of computational chemistry and molecular modelling, this study is to provide more information about the interactions between some novel synthesized benzimidazole derivatives with NS5B polymerase of HCV, thereby evaluating the potential for developing into a novel HCV inhibitor.